Peningkatan Motivasi Belajar Siswa dengan Menggunakan Media Video Based Learning di Pondok Pesantren An-Nur Tangkit - Yoga Ichlasul Amal; Hindun Hindun; Heri Darmawansah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is a Classroom Action Research (CAR), aimed at improving the learning motivation of class IX A students in the subject of Islamic Cultural History at the An-Nur Tangkit Muaro Jambi Islamic Junior High School by using Video Based Learning (VBL) media. This research was conducted in two cycles and four stages, including: (1) planning, (2) implementation, (3) observation, (4) reflection. Data were obtained through observation, interviews and documentation. The subjects of this research were class IX A students at the An-Nur Tangkit Muaro Jambi Islamic Junior High School, totaling 20 students. In the application of this Video Based Learning media, there was an increase in student learning motivation in each cycle. The value of student learning motivation in cycle I was 47.4% with a moderate category, and the value of student learning motivation in cycle II was 66.9% with a high category. Which means that through the use of Video Based Learning (VBL) media, student learning motivation can be improved.